Midwifery Care of Pregnancy in Pregnant Women with Anemia - Miftaqul Jannah; Ira titisari; Dwi estuning rahayu; Finta isti kundarti; Rahajeng sisti nur rahmawati (KHD Production, 2025)
Pregnancy anemia is a condition where the hemoglobin level in the blood falls below normal due to a decrease in the number of erythrocytes or hemoglobin, thereby reducing the blood's ability to carry oxygen to the vital organs of the mother and fetus. The aim of this study is to determine the effectiveness of a combination of iron (Fe) tablets and dates in addressing anemia. This research uses a case study approach, which aims to explore a phenomenon in depth within clearly defined boundaries. Data were comprehensively collected from various sources and documented using the SOAP method (Subjective, Objective, Assessment, Plan), providing a complete understanding of the case involving the respondent. The main focus of this study is on the phenomena arising from complaints and examination results during the period of midwifery care. The study was conducted on Mrs. DN at 38 weeks of gestation with moderate anemia, and the intervention provided consisted of the consumption of Fe tablets and 7 dates per day for 14 days. The results of the 2-week intervention showed successful outcomes for moderate pregnancy anemia, with an increase in hemoglobin levels from 9.2 g% to 9.9 g%. The case analysis established is Mrs. DN at 38 weeks of gestation with moderate anemia. The conclusion of this study is that the combination of Fe tablets and 7 dates per day for 14 days is effective as an intervention for managing moderate pregnancy anemia.